2019
DOI: 10.1177/2045894019862138
|View full text |Cite
|
Sign up to set email alerts
|

Oral treprostinil use in children: a multicenter, observational experience

Abstract: Pulmonary arterial hypertension is a progressive, incurable disease that occurs in adults and children alike. Therapeutic options for children are limited and infrequently described, including newer agents such as treprostinil, an oral prostanoid. Herein, we describe the pooled pediatric experience in 28 patients from four pediatric pulmonary hypertension programs over two years. This descriptive, observational study describes the various methods of initiation of oral treprostinil in both prostanoid-naïve pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…23,29,30 The remaining 16 retrospective studies reported data from small cohorts (1-85 patients), including 1 controlled31 (children with congenital diaphragmatic hernia receiving treprostinil vs. children with congenital diaphragmatic hernia without treprostinil) and 5 multicenter studies. 11,21,[32][33][34] Most authors suggested that treprostinil was an alternative to treat pediatric PH (Table 1). 29,35 However, no data from pediatric randomized controlled trials were reported in the literature, and currently treprostinil has only been approved in adult PAH treatment by European and US drug agencies (Table 2).…”
Section: Literature Reviewmentioning
confidence: 99%
“…23,29,30 The remaining 16 retrospective studies reported data from small cohorts (1-85 patients), including 1 controlled31 (children with congenital diaphragmatic hernia receiving treprostinil vs. children with congenital diaphragmatic hernia without treprostinil) and 5 multicenter studies. 11,21,[32][33][34] Most authors suggested that treprostinil was an alternative to treat pediatric PH (Table 1). 29,35 However, no data from pediatric randomized controlled trials were reported in the literature, and currently treprostinil has only been approved in adult PAH treatment by European and US drug agencies (Table 2).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Treprostinil is also available as extended‐release tablets (trade name, Orenitram®) and has been used in lower risk, stable pediatric PAH patients transitioning from parenteral treprostinil, inhaled treprostinil, or as a new adjunct therapy 62,63 . While the oral route offers many advantages, use of enteral treprostinil in young pediatric patients is limited because the tablets cannot be cut or crushed and must be swallowed whole 64 .…”
Section: Prostacyclin Analoguesmentioning
confidence: 99%
“…While the oral route offers many advantages, use of enteral treprostinil in young pediatric patients is limited because the tablets cannot be cut or crushed and must be swallowed whole 64 . Similar to the adult studies, GI side effects like nausea, vomiting, and diarrhea which often can be dose‐limiting, were common among pediatric patients 62,63,65 . To minimize the peak to trough ratio that is theorized to contribute to adverse effects, three‐time a day dosing is recommended over twice‐daily dosing and better mimics continuous parenteral treprostinil concentrations 65,66 .…”
Section: Prostacyclin Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…The common adverse effects when admitted subcutaneously are infusion site pain and bleeding. Inhaled and oral form of this medication are also available in some countries [36,37].…”
Section: Restoring Prostaglandins Of the Endothelial Cellsmentioning
confidence: 99%